2022
DOI: 10.3390/nano12244394
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Passing Vehicle Search Algorithm for Optimization of WEDM Process of Nickel-Based Superalloy Waspaloy

Abstract: Nickel-based superalloys find their main use in missile engines, atomic devices, investigational aircraft, aerospace engineering, industrial applications, and automotive gas turbines, spacecraft petrochemical tools, steam power, submarines, and broader heating applications. These superalloys impose certain difficulties during the process fabrication owing to their levels of higher hardness. In the current study, the precise machining of Waspaloy was attempted through the wire electrical discharge machining (WE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 78 publications
(94 reference statements)
0
2
0
Order By: Relevance
“… Reference Methodology Adopted Improvements of this study Nain et al [ 29 ] Used SVM to predict the MRR and SR The MRR improved by 74.75 %, and SR 63.63 % Varun and Venkaiah [ 30 ] GRA coupled with GA The MRR enhanced by 95 %. Chaudhari et al [ 36 ] Optimization using PVS Algorithm The MRR improved by 98 %, however, SR depreciated by 60.94 % Chaudhari et al [ 37 ] Optimization using PVS Algorithm The MRR enhanced by 97.55 % and SR depreciated by 53.37 % …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Reference Methodology Adopted Improvements of this study Nain et al [ 29 ] Used SVM to predict the MRR and SR The MRR improved by 74.75 %, and SR 63.63 % Varun and Venkaiah [ 30 ] GRA coupled with GA The MRR enhanced by 95 %. Chaudhari et al [ 36 ] Optimization using PVS Algorithm The MRR improved by 98 %, however, SR depreciated by 60.94 % Chaudhari et al [ 37 ] Optimization using PVS Algorithm The MRR enhanced by 97.55 % and SR depreciated by 53.37 % …”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that by feeding the MWCNT in the dielectric during WEDM process enhanced the MRR by 35.85 %, reduced the SR and RLT by 42.66 % and 40.07 %, respectively. In another study, Chaudhari et al [ 37 ] attempted to WEDM the Ni-based superalloy (Waspaloy) by employing the MWCNT with different processing parameters. The multi-objective optimization suggested the improvement of 65.70 % in MRR, 50.68 % in SR, and 40.96 % in RLT when 1 g/L MWCNT were engaged in the dielectric fluid during the machining process.…”
Section: Introductionmentioning
confidence: 99%
“…However, the machined surface of PMWEDM obtained using the same machining parameters as the standard WEDM method exhibited a significant improvement in surface defects, i.e., a significant reduction in micro-pores, globules, and micro-cracks. The consistent sparking between the work material and the tool reduces microcracks significantly in the PMWEDM process [67,68]. The significant gap between the tool and the workpiece is the cause of the large reduction in deposition of debris (globules) and micro-pores in the NPMWEDM process [69].…”
Section: Effect Of Expanded Graphite On Surface Morphologymentioning
confidence: 99%